2022
DOI: 10.1007/s00784-022-04658-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparative histological study of the effect of TheraCal LC and biodentine on direct pulp capping in rabbits: an experimental study

Abstract: Objectives This study histologically compared the effect of TheraCal LC and biodentine on direct pulp capping using a rabbit model. Materials and methods A direct pulp capping procedure was performed on 40 mandibular central incisors of 20 healthy, male New Zealand white rabbits. TheraCal LC and biodentine were applied to exposed pulp and 10 randomly selected rabbits were euthanized after the first and second week. Incisors were extracted and prepared for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
9
0
4
Order By: Relevance
“…This greater porosity of Bioaggregate may be a contributing factor in the dense mineralized dentine formation with Bioaggregate reported in the study by Kim et al [38]. Kayad et al [39] in the second week, while Biodentine created a significantly thicker dentine bridge in the first and second weeks. The results of a randomized clinical trial showed that TheraCal was less successful than Biodentine but better than Dycal when evaluated clinically and radiographically [40].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This greater porosity of Bioaggregate may be a contributing factor in the dense mineralized dentine formation with Bioaggregate reported in the study by Kim et al [38]. Kayad et al [39] in the second week, while Biodentine created a significantly thicker dentine bridge in the first and second weeks. The results of a randomized clinical trial showed that TheraCal was less successful than Biodentine but better than Dycal when evaluated clinically and radiographically [40].…”
Section: Discussionmentioning
confidence: 74%
“…Since the DPSCs, which play a role in forming reparative dentine, can be positioned in the porous structure of Bioaggragate, its porous structure may also play a role in the success of pulp capping treatment. However, in in vivo studies [12,33,39,40,48,49] performed with other, less porous pulp capping materials, successful results were obtained. Thus, further studies should be conducted to determine which properties of the materials used in the pulp capping treatment primarily affect the success.…”
Section: Discussionmentioning
confidence: 99%
“…Further products marketed with shorter setting times are Biodentine [122][123][124][125][126][127][128][129], Endocem MTA [130][131][132][133], MTA Bio [134,135], EndoSeal MTA [136,137] and MTA Fillapex [138][139][140][141][142][143]. A setting time of as little as 0.3 min has been reported for TheraCal [144][145][146][147][148] because of the use of resin and light cure technology. The radiopacifying agent used is another important element that has been studied for the improvement of these products.…”
Section: Calcium Silicatesmentioning
confidence: 99%
“…6,7 This restoration is required to seal the exposed area and induce differentiation of dental pulp stem cells into odontoblast-like cells for reparative dentine production. 8 The capping material employed in direct capping processes has been identified as a key element in treatment effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…9,11,14 MTA disadvantages, such as lengthy setting time and probable discoloration, prompted the development of additional calcium silicatebased polymers, such as biodentine, to address these shortcomings and increase physiochemical qualities. 7,8,14 Tideglusib is a glycogen synthase kinase-3 (GSK-3) inhibitor that belongs to the thiadiazolidine family. It prevents inflammation and neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%